Development of Stir-fried Chilli Paste with Protein Supplementation from Khai Phum - Phugan, Pakawadee; Amdonkloy, Suphakron; Sirirut, Kamonrut; Choosing, Suwanan (Journal of Food Health and Bioenvironmental Science, 2018)
This research is the development of stir-fried chilli paste additive protein from Khai Phum. The objectives were 1) to add more nutrients in the stir-fried chili paste 2) to study consumers’ acceptance, chemical composition and microbial quality of the product by adding 3 different swamp algae: 20, 30 and 40% which calculated from the total raw material weight. The result of consumers’ acceptance with 100 participants showed that the fried chili paste with 30% of swamp algae obtained the highest scored in perception aspect. The Stir-fried chili paste with 30% of swamp algae could significantly increase nutritive values such as carbohydrate, beta-carotene and calcium. In particular, beta-carotene was increased 25449 micrograms and calcium was increased 354.9 milligrams from the basic recipe. In 100 grams of the fried chili paste with 30% of Khai Phum consisted 24.47±0.04% of protein, 25.41±0.16% of carbohydrate, 8.85±0.11% of fat, 32.33±0.17% of moisture and 8.94±0.05% of ash. Adding more swamp algae in the product decreased brightness and red value. On the other hand, it increased green value. Moreover, increasing more swamp algae slightly decreased aw value in the product. The result of microbial quality test indicated that microbial quality of the fried chili paste with 30% of swamp algae was in according to the community product standard.